1992
DOI: 10.1038/bjc.1992.329
|View full text |Cite
|
Sign up to set email alerts
|

Malignant progression of a mouse fibrosarcoma by host cells reactive to a foreign body (gelatin sponge)

Abstract: Summary The QR regressor tumour (QR-32), a fibrosarcoma which is unable to grow progressively in normal syngeneic C57BL/6 mice, was able to grow progressively in 13 out of 22 mice (59%) when it was subcutaneously coimplanted with gelatin sponge. We established four culture tumour lines from the resultant tumours (QRsP tumour lines). These QRsP tumour lines were able to grow progressively in mice even in the absence of gelatin sponge. The ability of QRsP tumour cells to colonise the lungs after intravenous inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 13 publications
4
78
0
Order By: Relevance
“…We have also observed that PGE2 acts not only as an immunosuppressive factor but also as a positive factor for the chemotactic and motile behaviour of tumour cells (Young et al, 1991). These previous observations revealed that enhanced PGE2 production by tumour cells results in the malignant progression of the tumour cells (Okada et al, 1992). QR-32 cells produce large amounts of PGE2 when the tumour cells have been co-cultured with foreign body-reactive cells (Okada et al, 1992).…”
Section: Cytolysis Of Qr-32 Cells By Various Anti-tumour Effector Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also observed that PGE2 acts not only as an immunosuppressive factor but also as a positive factor for the chemotactic and motile behaviour of tumour cells (Young et al, 1991). These previous observations revealed that enhanced PGE2 production by tumour cells results in the malignant progression of the tumour cells (Okada et al, 1992). QR-32 cells produce large amounts of PGE2 when the tumour cells have been co-cultured with foreign body-reactive cells (Okada et al, 1992).…”
Section: Cytolysis Of Qr-32 Cells By Various Anti-tumour Effector Cellsmentioning
confidence: 99%
“…We found that the threshold level of POE2 production necessary to suppress host immune reactivity in vivo is equivalent to approximately 6,000pgml-' of medium in vitro, a value which was produced by 1 x 104 tumour cells during a 48 h culture (Okada et al, 1990(Okada et al, , 1992. Japan).…”
Section: Twnour Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the anti-tumour effects of chemoimmunotherapy with CY and lentinan are T cell dependent (M Suzuki et al, unpublished results), host inflammatory cells may be involved in the tumour disruption process. Recent reports demonstrated that oxygen radicals produced by host inflammatory cells induced the augmentation of PGE2 production by tumour cells and that the enhanced production of PGE2 from tumour cells is closely related to the phenotype changes of tumour cells from benign to malignant (Okada et al, 1990(Okada et al, , 1992(Okada et al, , 1994. The elucidation of exact mechanisms for the increased production of PGE2 during therapy requires further detailed studies.…”
Section: Disussionmentioning
confidence: 99%